THE SPORTS CAMP - FUNCTIONING SPECIFIC AND MANAGERIAL SPECIFIC IN THE GLOBALIZATION CONTEXT - Nichifor Florin (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
The purpose of the research is to analyze the elements of cultural specificity of the OglinziTârguNeamţ sports camp, with a focus on the following aspects: the activity of the manager and of the managerial team, employees' attitude, the behaviour of clients (children, students, young people, teenagers, athletes), the mental, behavioural, and attitudinal conditions in the context of globalization. Usually considered by children and teenagers the most exciting and attractive space, the camp attracts people every year, thus "producing" the most beautiful and intense memories. The camp is the place where the clients look for sports activity, relaxation, entertainment, and rest. At the same time, it becomes, for a shorter or longer period, a special institution, a community. For any client, the camp means emotion, surprise, knowledge, meeting expectations. The client also has the possibility of developing practical (sports) and communicational skills, of getting used to the spirit of teamwork, of expressing and developing new creative skills, of getting in contact with the customs, traditions, and culture of the area.